Alteration of the tertiary structure of the major bee venom allergen Api m 1 by multiple mutations is concomitant with low IgE reactivity - Buhot, Cécile (Cold Spring Harbor Laboratory Press, 2004)
We have engineered a recombinant form of the major bee venom allergen (Api m 1) with the final goal of reducing its IgE reactivity. This molecule (Api mut) contains 24 mutations and one deletion of 10 amino acids. The successive introduction of these sequence modifications led to a progressive loss of specific IgE and IgG reactivity and did not reveal any immunodominant epitopes. However, Api mut exhibited a clear loss of reactivity for Api m 1-specific IgE and IgG. Injection of Api mut into mice induced specific antibody production. This humoral response was as high as that induced by the Api m 1 but the cross-reactivity of the antibodies was weak. As inferred by far UV circular dichroism, this mutant was correctly folded. However, near UV circular dichroism and denaturation curves of Api mut showed that it exhibits a dynamic tertiary structure and that it is a highly flexible molecule. Finally, as all the sequence modifications have been introduced outside the human and murine T cell epitope regions, we investigated its T cell properties in mice. We showed that Api mut-specific T lymphocytes induced in vivo were stimulated in vitro by both proteins. These data provide new insights in the design of hypoallergenic molecules.